Experiencing the advantages of Indonesian Islamic Higher Education: UIN Malang international student’s perspectives and overviews - Azzeehavella, Najiyya Najat; Alfiyah, Dina; Setiawan, Geritza Rabbani; Rosi, Rois Imron (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This study aims to deeply explore the perspectives and overviews of international students at UIN Malang regarding their experience on several advantages afforded by Indonesian Islamic higher education. As the world’s largest Muslim population, Indonesia has emerged as a compelling destination for international students seeking an education. Their experiences of studying and interacting with Indonesian lecturers and peers, as well as the advantages of Indonesian education can be a useful for every element of Indonesian policymakers. This study can be more crucial because there are many researches stated that Indonesian educational systems are relatively poor compared to other countries in term of teacher’s quality, material, and learning strategies and often explored many disadvantages from Indonesian education.  Using qualitative data with phenomenological design, this study explored 14 international students coming from 10 countries including Tajikistan, China, The United State of America, Yaman, Afghanistan, Comoro, Cambodia, Pakistan, Sudan, and Thailand. The result stated that there the international students of UIN Malang experienced four specific advantages within Indonesian Islamic higher education those are; the Indonesian lecturers are caring, friendly, and respectful, Indonesian classroom are interactive and full of strategies, the Islamic environment around university able to support the enjoyment of learning, and the existence of peer-teaching within Indonesian context of learning is contributed to the material understanding. The result of this study can be a proof that there are several advantages of Indonesian education that can be promoted to the realm of global education.